Controversial Pan Accounts Still In Valley Harps Hands - Unknown (Trinidad Guardian)
At a special convention of the steelbandsmen organisation, Pan Trinbago, which was convened to receive audited accounts, Mr. Roy Augustus, President and three other executive officers resigned their posts. After these resignations, a vote of 'no confidence' was passed in the rest of the executive. Disputed financial documents of Pan Trinbago for 1971-1973 remained in the hands of Mr. Gary Simmons of Valley Harps Steelband of Diego Martin as an accountant refused to audit the documents.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Financial statements, Unaudited -- Trinidad and Tobago; Pan Trinbago (Organization); Steel band music -- Trinidad and Tobago